2000
DOI: 10.1159/000018321
|View full text |Cite
|
Sign up to set email alerts
|

Primary Atrophic Profound Linear Scleroderma

Abstract: We present 3 unusual cases of deep linear, primary atrophic scleroderma, not preceded by inflammatory reaction and sclerosis, involving the subcutis and deeper tissues. These cases differ in the course and prognosis from typical profound scleroderma since they do not lead to disfiguration and crippling deformities. In contrast to the atrophies left after regression of morphea or linear scleroderma, they do not involve the dermis, which does not show discoloration or changes in texture. Infiltrates in the endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
3
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 10 publications
(15 reference statements)
1
12
3
3
Order By: Relevance
“…Thus, the features were similar to those described by Jablonska and colleagues [10 ]in 3 patients with primary atrophic profound scleroderma. However, in these cases, the involvement was linear, band-like and more extensive.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the features were similar to those described by Jablonska and colleagues [10 ]in 3 patients with primary atrophic profound scleroderma. However, in these cases, the involvement was linear, band-like and more extensive.…”
Section: Discussionsupporting
confidence: 88%
“…There are no reliable histological criteria to differentiate PRS from involutionary scleroderma. Recently, Blaszczyk et al [7] reported three cases of primary atrophic profound linear scleroderma with involvement of the subcutis and deeper tissues. In accordance with a previous report of Malandrini et al [8], deep skin biopsies showed inflammatory infiltrates in the endomysium and perimysium.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, atrophy was not preceded by clinical evidence of inflammation, discoloration of the skin, or sclerosis. Blaszczyk et al [7] concluded that PRS could be regarded as a variety of deep linear scleroderma [7,9]. …”
Section: Discussionmentioning
confidence: 99%
“…Blaszczyk et al 4 delineated primary atrophic profound linear scleroderma ( = deep atrophy of subcutis and deeper tissues without preceding inflammatory changes) as a new entity. Accordingly, the distinct muscle atrophy of our patient may be a primary atrophic profound linear scleroderma followed by the classical form of linear scleroderma.…”
mentioning
confidence: 99%